Fast hydropyrolysis of biomass Conversion: A comparative review - Oh, Shinyoung; Lee, Jechan; Lam, Su Shiung; Kwon, Eilhann E.; Ha, Jeong-Myeong; Tsang, Daniel C. W.; Ok, Yong Sik; Chen, Wei-Hsin; Park, Young-Kwon (ELSEVIER SCI LTD, 2021)
Recent studies show that fast hydropyrolysis (i.e., pyrolysis under hydrogen atmosphere operating at a rapid heating rate) is a promising technology for the conversion of biomass into liquid fuels (e.g., bio-oil and C4+ hydrocarbons). This pyrolysis approach is reported to be more effective than conventional fast pyrolysis in producing aromatic hydrocarbons and also lowering the oxygen content of the bio-oil obtained compared to hydrodeoxygenation (a common bio-oil upgrading method). Based on current literature, various non-catalytic and catalytic fast hydropyrolysis processes are reviewed and discussed. Efforts to combine fast hydropyrolysis and hydrotreatment process are also highlighted. Points to be considered for future research into fast hydropyrolysis and pending challenges are also discussed.